Firm-specific determinants of the extent of compliance with international accounting standards in the corporate annual reports of companies listed on the Egyptian Stock Exchange: a positive accounting approach. (16th April 2009) - Samaha, Khaled; Stapleton, Pamela
This paper examines the firm specific characteristics – as a proxy for positive accounting research – that are associated with the propensity of companies listed on the Cairo and Alexandria Stock Exchanges (CASE) to comply with the newly harmonised Egyptian Accounting Standards (EASs) issued in 1997 and that are close to the international accounting standards (IASs). Although having an international audit firm is the dominant factor associated with disclosure and measurement/presentation compliance, ownership concentration, share trading, size as measured by market capitalisation and internationality are also associated with compliance. However, the results show that profitability, liquidity and leverage do not seem to affect the extent of compliance with EASs and the performance of manufacturing are at par with non-manufacturing firms. Also the performance of private sector firms is at par with public sector firms. This may indirectly imply that the positive accounting perspective may not be entirely applicable for de facto compliance in Egypt. Hence, it cannot be entirely inferred that listed Egyptian companies may use de facto compliance with EASs as a means of reducing agency costs, raising capital, reducing political costs or signalling to the market that they are high quality firms.